2008
DOI: 10.1073/pnas.0806521105
|View full text |Cite
|
Sign up to set email alerts
|

Structure and DNA binding of alkylation response protein AidB

Abstract: Exposure of Escherichia coli to alkylating agents activates expression of AidB in addition to DNA repair proteins Ada, AlkA, and AlkB. AidB was recently shown to possess a flavin adenine dinucleotide (FAD) cofactor and to bind to dsDNA, implicating it as a flavindependent DNA repair enzyme. However, the molecular mechanism by which AidB acts to reduce the mutagenic effects of specific DNA alkylators is unknown. We present a 1.7-Å crystal structure of AidB, which bears superficial resemblance to the acyl-CoA de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(60 citation statements)
references
References 28 publications
3
54
2
Order By: Relevance
“…As expected, the construct that expresses only the DNA binding domain (AidB I-III) showed no IVD activity. These findings clearly indicated that AidB I-III is responsible for its catalytic activity, as predicted by structural analyses (2).…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…As expected, the construct that expresses only the DNA binding domain (AidB I-III) showed no IVD activity. These findings clearly indicated that AidB I-III is responsible for its catalytic activity, as predicted by structural analyses (2).…”
Section: Resultssupporting
confidence: 49%
“…Means and standard deviations have been calculated from four independent assays. residues, comprise the acyl-CoA dehydrogenase activity, and domain IV comprises the DNA binding activity (2). In order to determine whether the entire protein is required for the repressor activity or if the acyl-CoA dehydrogenase domain is dispensable, we constructed plasmids that express only the dehydrogenase domain or the DNA binding domain and tested them for AidB regulatory activity in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular replacement was used to determine the crystal structure of cVLCAD using the structure of E. coli AidB (PDB code 3djl; Bowles et al, 2008), which has 30% sequence identity to cVLCAD, as a search model. One unique solution with two monomers was obtained with a likelihood score of 310.8 and a Z score of 16.7 using the program Phaser (McCoy et al, 2007;Collaborative Computational Project, 1994).…”
Section: Resultsmentioning
confidence: 99%